Pemberdayaan Masyarakat dalam Meningkatkan Ekonomi Lokal Melalui Produksi Kain Tenun Songket di Kabupaten Labuhanbatu - Ari Gunawan; Nurintan Asyiah Siregar; Muhammad Yasir Arafat Pohan (Pusat Riset dan Inovasi Nasional, 2025)
Empowerment activities as an approach to improve the ability and potential of songket woven cloth craftsmen to be more empowered, such as increasing skills, increasing market access, and encouraging progress in socio-economic conditions. Songket woven cloth, which is a cultural heritage, not only has aesthetic value but also significant economic potential. By involving the community in the production process, from processing raw materials to marketing, it is expected to create jobs, increase income, and preserve traditions. Training programs and marketing support are key to empowering local craftsmen, so that they can compete in a wider market. Through collaboration between the government, non-governmental organizations, and the private sector, it is hoped that the production of songket woven cloth can become a driving force for a sustainable economy in Labuhanbatu Regency.